Microcystin kinetics (bioaccumulation and elimination) and biochemical responses in common carp (Cyprinus carpio) and silver carp (Hypophthalmichthys molitrix) exposed to toxic cyanobacterial blooms - Adamovský, Ondrej; Kopp, Radovan; Hilscherová, Klára; Babica, Pavel; Palíková, Miroslava; Pasková, Veronika; Navrátil, Stanislav; Marsálek, Blahoslav; Bláha, Ludek (Environmental toxicology and chemistry, 2007)
Two species of common edible fish, common carp (Cyprinus carpio) and silver carp (Hypophthalmichthys molitrix), were exposed to a Microcystis spp.-dominated natural cyanobacterial water bloom for two months (concentrations of cyanobacterial toxin microcystin, 182-539 microg/g biomass dry wt). Toxins accumulated up to 1.4 to 29 ng/g fresh weight and 3.3 to 19 ng/g in the muscle of silver carp and common carp, respectively, as determined by enzyme-linked immunosorbent immunoassay. Concentrations an order of magnitude higher were detected in hepatopancreas (up to 226 ng/g in silver carp), with a peak after the initial four weeks. Calculated bioconcentration factors ranged from 0.6 to 1.7 for muscle and from 7.3 to 13.3 for hepatopancreas. Microcystins were completely eliminated within one to two weeks from both muscle and hepatopancreas after the transfer of fish with accumulated toxins to clean water. Mean estimated elimination half-lives ranged from 0.7 d in silver carp muscle to 8.4 d in common carp liver. The present study also showed significant modulations of several biochemical markers in hepatopancreas of fish exposed to cyanobacteria. Levels of glutathione and catalytic activities of glutathione S-transferase and glutathione reductase were induced in both species, indicating oxidative stress and enhanced detoxification processes. Calculation of hazard indexes using conservative U.S. Environmental Protection Agency methodology indicated rather low risks of microcystins accumulated in edible fish, but several uncertainties should be explored.
Keywords: tkáňová distribuce; mikrocystiny; Muscles; Environmental Monitoring; Microcystins; monitorování životního prostředí; Tissue Distribution; kapři; toxiny kmene Cyanobacteria; Cyanobacteria Toxins; kinetika; Marine Toxins; Animals; svaly; játra; zvířata; Carps; Bacterial Toxins; Liver; Kinetics; mořské toxiny; bakteriální toxiny